2018
DOI: 10.5897/jcab2017.0455
|View full text |Cite
|
Sign up to set email alerts
|

Camel milk improvement of antioxidant and lipid profile in hypercholesterolemic rabbits

Abstract: Dietary intervention can improve lipid profile and therefore impede the progress of atherosclerosis. The primary aim of this study is to assess the possible role of camel milk in enhancing the antioxidant capacity in rats fed a high fat diet. Thirty rabbits were individually divided into three groups, the control, HFD and HFD with camel milk. The control group fed on 100 g/day of NOR diet rabbit chow (USA) for three months; whereas the HFD group will be fed rabbit diet supplemented with 1.0% cholesterol plus 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The present findings drawn from human studies were consistent with prior research in animal models that demonstrated CM intake had beneficial effects in improving lipid profiles of chemically-induced diabetes. CM was reported to decrease TC, TG, and HDL cholesterol [ 75 ], and may also decrease the synthesis of hepatic cholesterol [ 76 ]. In a study involving rabbits, CM significantly reduced TC, TG, and HDL [ 75 ], with this cholesterol-lowering effect ascribed to improvement in the body’s oxidative status via a reduction in the catalase and peroxidase enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present findings drawn from human studies were consistent with prior research in animal models that demonstrated CM intake had beneficial effects in improving lipid profiles of chemically-induced diabetes. CM was reported to decrease TC, TG, and HDL cholesterol [ 75 ], and may also decrease the synthesis of hepatic cholesterol [ 76 ]. In a study involving rabbits, CM significantly reduced TC, TG, and HDL [ 75 ], with this cholesterol-lowering effect ascribed to improvement in the body’s oxidative status via a reduction in the catalase and peroxidase enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…CM was reported to decrease TC, TG, and HDL cholesterol [ 75 ], and may also decrease the synthesis of hepatic cholesterol [ 76 ]. In a study involving rabbits, CM significantly reduced TC, TG, and HDL [ 75 ], with this cholesterol-lowering effect ascribed to improvement in the body’s oxidative status via a reduction in the catalase and peroxidase enzymes. Increased fecal excretion of cholesterol, improved hepatic glutathione peroxidase, and attenuated hepatic thiobarbituric acid were other plausible mechanisms for the lipid-lowering effect of CM demonstrated in animal models [ 75 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation